PELAKSANAAN PRINSIP-PRINSIP PENANGANAN GELANDANGAN DAN PENGEMIS PASCA PENERTIBAN DI KOTA PEKANBARU - Erfan Setiawan; Zaili Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Handling is better done by the Department of Social and Pekanbaru City Cemetery to the provision of rehabilitation, providing guidance in the form of mental health counseling, as well as religious guidance. Once the guidance is done, then to every homeless and beggars can be given for the provision of basic skills training, skills which will be used when they are released back into normal society.The purpose of this study is to see how the implementation of the principles of handling vagrants and beggars in the city pekanbaru and to know which one is the dominant factor in this study. To see what factors are the bottlenecks in the implementation of the principles of handling vagrants and beggars in the city of Pekanbaru researchers saw from Gibson's theory (2007). This research was conducted in the social services and burial city of Pekanbaru. In conducting the data collection methods used observation and in-depth interviews to research informants. Once the data is collected and then drawn conclusions based on the laws of inference and analyzed using qualitative descriptive analysis.After a study found that the factors that become barriers to the implementation of the principles of handling vagrants and beggars in the city of Pekanbaru is among other factors the absence of shelter or rehabilitation center, the lack of government funding, social services employees who do not have the understanding and expertise in implementing the principle of The treatment principles, and the ineffectiveness of regulation ni 12 of 2008 on the social order in the city of Pekanbaru.Keywords: implementation, management principles, vagrants and beggars.